Substance P/ Neurokinin-1 Receptor, Trigeminal Ganglion, Latency, and Coronavirus Infection-Is There Any Link? - Mehboob, Riffat; Kurdi, Maher; Bamaga, Ahmed; Aldardeir, Njoud; Nasief, Hisham; Moshref, Leena H.; Alsinani, Taghreed; Rayes, Almotasimbellah O.; Jabbad, Reem H. (Frontiers in Medicine, 2021)
Novel Severe Acute Respiratory Syndrome-Corona Virus-2 infection (SARS-CoV-2) is an acute respiratory and infectious disease. This perspective aims to provide a basic understanding of the inflammation caused by SARS-CoV-2 and its relation to the trigeminal ganglion (TG). The virus enters through the mucous membranes of the orofacial region and reaches the TG, where it resides and takes control of its peptides including Substance P (SP). SP is the main neuropeptide, neuromodulator, and neuro-hormone of TG, associated with nociception and inflammation under noxious stimulus. SP release is triggered and, consequently, affects the immune cells and blood vessels to release the mediators for inflammation. Hence, cytokine storm is initiated and causes respiratory distress, bronchoconstriction, and death in complicated cases. Neurokinin-1 Receptor (NK-1R) is the receptor for SP and its antagonists, along with glucocorticoids, may be used to alleviate the symptoms and treat this infection by blocking this nociceptive pathway. SP seems to be the main culprit involved in the triggering of inflammatory pathways in SARS-CoV-2 infection. It may have a direct association with cardio-respiratory rhythm, sleep-wake cycle, nociception, and ventilatory responses and regulates many important physiological and pathological functions. Its over-secretion should be blocked by NK-1R antagonist. However, experimental work leading to clinical trials are mandatory for further confirmation. Here, it is further proposed that there is a possibility of latency in SARS-CoV-2 virus infection if it is acting through TG, which is the main site for other viruses that become latent.